IMPLEMENTASI PROGRAM KETENAGAKERJAAAN PADA KANTOR DINAS TENAGA KERJA KOTA MAKASSAR - Idris, Ardianti (Universitas Teuku Umar, 2023)
This study aims to analyze the implementation of the employment program by the Makassar City Manpower Office using qualitative descriptive methods. Data were collected through interviews, observations, and documentation from relevant informants. The analysis focused on four aspects: communication, resources, disposition (attitude of implementers), and organizational structure. The results indicate that program implementation has been running quite well. Communication is carried out through social media, outreach, and job fairs. Despite limited staff and facility resources, the program remains optimal. The disposition of implementers demonstrates a good work attitude, responsibility, and loyalty. The organizational structure demonstrates good division of tasks and coordination. Overall, the program has been effective, although some technical challenges still need improvement.Keywords : Implementation, Employment Program, Manpower Office, Communication, Resources, Disposition, Organizational Structure